2(3x-4)+7(4-x)=4x

Simple and best practice solution for 2(3x-4)+7(4-x)=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-4)+7(4-x)=4x equation:


Simplifying
2(3x + -4) + 7(4 + -1x) = 4x

Reorder the terms:
2(-4 + 3x) + 7(4 + -1x) = 4x
(-4 * 2 + 3x * 2) + 7(4 + -1x) = 4x
(-8 + 6x) + 7(4 + -1x) = 4x
-8 + 6x + (4 * 7 + -1x * 7) = 4x
-8 + 6x + (28 + -7x) = 4x

Reorder the terms:
-8 + 28 + 6x + -7x = 4x

Combine like terms: -8 + 28 = 20
20 + 6x + -7x = 4x

Combine like terms: 6x + -7x = -1x
20 + -1x = 4x

Solving
20 + -1x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
20 + -1x + -4x = 4x + -4x

Combine like terms: -1x + -4x = -5x
20 + -5x = 4x + -4x

Combine like terms: 4x + -4x = 0
20 + -5x = 0

Add '-20' to each side of the equation.
20 + -20 + -5x = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -5x = 0 + -20
-5x = 0 + -20

Combine like terms: 0 + -20 = -20
-5x = -20

Divide each side by '-5'.
x = 4

Simplifying
x = 4

See similar equations:

| X-2(1)=-1 | | 4x+8=8-2x | | 7-4(3x-2)=9 | | -6-7m=72 | | 3x^3+12x^2+16x+8=0 | | 5x^4-25x^2=0 | | (6-x)(x+6)-(x-11)=36 | | 9+10k=119 | | 7x-7=6x+9 | | 8(5y+x)=4fory | | 77=7(n-1) | | -2w=-7w-10 | | -77=-5+9m | | 23=7+2x-4 | | 7x-57=48+2x | | 162=-9(x+1) | | -48=132-10 | | mk-nm=gs | | (5.3*7)+(x*3)=55 | | (5.3*7)+(x*3)=5.5 | | -18=-(p+4) | | (-4y^2)(-2y^8)= | | 9.82*x^2=2 | | -48=132-10x | | 3x^2-8xy-6y^2=-9 | | (5+-20)(20+-5)=0 | | 4x^2-8xy-6y^2=-9 | | 4x=27+8 | | 30x+40x=35(x+x) | | 6-6n=-5n | | 8+4s-1=9s+16-6s | | Y=(-5)x+5 |

Equations solver categories